2018
DOI: 10.1177/0391398818763478
|View full text |Cite
|
Sign up to set email alerts
|

‘Real-life’ experience with direct-acting antiviral agents for hepatitis C virus in end-stage renal disease

Abstract: All-oral, interferon-free therapy with direct-acting antiviral agents for chronic hepatitis C virus in advanced chronic kidney disease was effective and well tolerated in a 'real-life' clinical setting. Careful monitoring of haemoglobin and serum creatinine during therapy with direct-acting antiviral agents is suggested. Studies are under way to address whether sustained viral response translates into better survival in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…23,24 The SVR 12 rate from a recently published study ranged from (58-100% ) in patients with advanced CKD with Sofosbuvir based regimen. 25 In a multicenter experience of Sofosbuvir based regimens in end stage renal disease, the researchers measured plasma levels of Sofosbuvir and its active metabolite and confirmed the accumulation of active metabolite in plasma but it didn't led to any clinically significant adverse effects. The success rate in this trail was 88%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 The SVR 12 rate from a recently published study ranged from (58-100% ) in patients with advanced CKD with Sofosbuvir based regimen. 25 In a multicenter experience of Sofosbuvir based regimens in end stage renal disease, the researchers measured plasma levels of Sofosbuvir and its active metabolite and confirmed the accumulation of active metabolite in plasma but it didn't led to any clinically significant adverse effects. The success rate in this trail was 88%.…”
Section: Discussionmentioning
confidence: 99%
“…24 Anemia was noticed to be associated with the use of Ribavarin despite being used at lower doses. 25 Mostly the studies have used reduced dose (half or alternate day) of Sofosbuvir in these patients. In a multicenter observational prospective study, authors compared daily full dose of Sofosbuvir with thrice weekly dose and it was noticed that Sofosbuvir itself or its inactive metabolite didn't accumulate in plasma with either regimen in between the dialysis session and drug was well tolerated by the study population.…”
Section: Discussionmentioning
confidence: 99%
“…One major limitation of the information reported above is that it is mostly based on industry-funded studies, and these kinds of studies are more likely to be published if results are favourable [30]. However, numerous real-life studies on the same point have been completed supporting the conclusions reported above [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Pi-containing Sof-free Daas (Real World Studies)mentioning
confidence: 99%
“…On the other hand, dialysis patients are at increased risk of acquiring the virus due to poor hygiene, increased risk of nosocomial infection and lack of proper sterilization techniques along with improper handling of equipment. Hence, testing all dialysis patients at entry and periodically thereafter is recommended[ 66 , 67 ]. However, there is some controversy on the type of testing (serology or NAT) in these patients[ 68 ].…”
Section: Kidney Involvement In Chronic Hcv Infectionmentioning
confidence: 99%